Iterative Photoinduced Chain Functionalization as a Generic Platform for Advanced Polymeric Drug Delivery Systems. Issue 3 (2nd November 2017) - Samad, Assala Al; Bethry, Audrey; Janouskova, Olga; Ciccione, Jérémie; Wenk, Christiane; Coll, Jean‐Luc; Subra, Gilles; Etrych, Tomas; Omar, Fawaz El; Bakkour, Youssef; Coudane, Jean; Nottelet, Benjamin
Abstract: Advanced drug delivery systems (DDS) are easily designed following a photoiterative strategy. Multifunctional polymers are obtained by coupling building blocks of interest to an alkynated poly(ε‐caprolactone) (PCL) platform via an efficient thiol–yne photoaddition. Fine‐tuning over the design is achieved, as illustrated with targeting and enzyme‐responsive DDS. Abstract : A simple photochemical iterative procedure tackles the challenge of polymers multifunctionalization for biomedical applications.